The role of online peer support in pregnancy: A scoping review - Honor Morris; Maria Duaso; Marilyn Ijeomah-Orji; Lisa Akester; Jenny Roddy; Jayne Samples; Kate Heighway; Nigel Simpson; Tomasina Stacey (PLoS ONE, 2026)
Background Online peer support groups offer virtual spaces where members can share experiences, seek advice, and offer mutual support. While in-person peer support in pregnancy has shown benefits such as improved well-being and reduced isolation, limited research has explored online peer support groups. This scoping review aims to examine the types, contexts, and perceived benefits of online peer support for pregnant people. Methods A systematic search was conducted in five databases (Embase, Medline PsychInfo, MIDIRS and CINAHL) from inception to December 2024. Eligible studies examined online peer support accessed by pregnant participants with direct interaction. Thematic analysis was applied to identify structural factors influencing the functioning of online peer support groups. The Langford Conceptual Analysis of Social Support was used to categorise type of support. Findings A total of 27 studies were included. The findings highlighted several structural factors that influence the functioning of online peer support groups for pregnant people. Group size was identified as a key factor, with smaller groups promoting more meaningful interactions. Active moderators supported participant interaction and ensured information quality, while privacy settings, such as closed groups and anonymised participation, fostered safe discussions. Emotional support, such as expressions of empathy, reassurance, and encouragement, was the most reported benefit, followed by informational and appraisal support. Instrumental support was observed less frequently. Conclusion This scoping review identified key structural factors shaping the design and functioning of online peer support groups for pregnant people. Group size, active moderation, and privacy settings influenced participation and engagement. Further research is recommended to explore how these structural elements impact long-term engagement and overall effectiveness for pregnant people. This project is funded by the National Institute for Health and Care Research (NIHR) under its Research for Patient Benefit (RfPB) Programme (Grant Reference Number NIHR205347). The views expressed are those of the author(s) and not necessarily those of the NIHR or the Department of Health and Social Care.